Statistical analysis of cloud characteristics in Northwest China based on Fengyun satellite data. (15th October 2018) - Zhao, Mengyue; Wu, Jiaji; Jeon, Gwanggil; Guo, Xing
Summary: The northwest region in China located at arid and semiarid areas, atmospheric precipitation converted by the cloud is an important part of water resources, and if we fully utilize cloud for cloud‐water conversion to alleviate the scarcity of water, thereby it is particularly important to analyze the macroscopic characteristics and the changing trends of clouds in the northwest region. In this paper, the 2016 Level 1 data of Fengyun Satellite has been calibrated, corrected, and processed, using the improved multi‐spectral thresholding method to calculate cloud coverage and cloud classification data. The optical thickness inversion uses the SBDART (Santa Barbara DISORT Atmospheric Radiative Transfer) radiation transmission mode to establish a radiation look‐up table with optical thickness as a function variable under different conditions of observation geometry, underlying surface type, and atmospheric environment. The results show that the coverage of clouds in the northwest region accounts for about 45%, and the cloud coverage changes with the seasons. The classification of clouds mainly consists of high clouds, low clouds, and cumulonimbus. The optical thickness of clouds is largely distributed between 10 and 25.